Kitābah is the Language of Education and Culture; Historical Description Analysis - Hazaa, Zuhair Mubarrak; Faisal, Ahmad (Borneo Journal of Language and Education, 2024)
Kitābah (reading and writing) is one of the Islamic civilizations. Kitābah emerged as one aspect of the emergence of science in the world. As an important element of world civilization, kitābah plays a role in creating language as a sign of communication between people and nations. The role of kitābah is so important as a medium of education and teaching. The Prophet ordered the prisoners of Badr war to transform the knowledge of the kitābah to the Muslim community. Caliph Umar bin Abdul Aziz also initiated a follow-up to the Prophet's order through Ibn Shihab Az-Zuhri in writing Waraqāt al-Ḥadīṡ. Kitābah is knowledge sourced from Allah swt. This research is intended to emphasize that the real source of knowledge is Allah swt. Teaching through revelation to the prophet Hud alaihis salam is the language of education which is then developed to preserve and maintain human life as a caliph who provides education. This research uses a qualitative method based on a literature review. The researcher examined several significant references as the main reference in this study. The kitābah plays a major role as a language of education, spreading knowledge, and preserving culture. World civilization before and after Islam developed as the kitābah flourished. The codification of various sciences such as Tafsir of the Koran, Hadith, Jurisprudence, Geography, Hisab, Mathematics, Chemistry, and Medicine is a real thing from the role of the kitābah as the language of education and civilization.